Multiply (7–√) (−2–√) . Give an exact answer

5 answers

To simplify the expression, we can use the distributive property of multiplication.

(7 – √)-2 – √) = (7 * -2) + (7 * √) + (-√ * -2) + (-√ * √)

= -14 + 7√ + 2√ + √^2

= -14 + 9√ + √^2

Since √^2 = (√)^2 = 2, we have:

= -14 + 9√ + 2

= -12 + 9√

Therefore, the exact answer is -12 + 9√.
Multiply (7–√) (−2–√) . Give an exact answer.
Responses −14−−√ negative start root
14 end root
−72–√ negative 7 start root 2 end root
5–√ start root 5 end root 14−−√
To multiply (7–√)(−2–√), we can use the distributive property.

First, multiply 7 with -2:

7 * -2 = -14.

Next, multiply 7 with -√:

7 * -√ = -7√.

Then, multiply -√ with -2:

-√ * -2 = 2√.

Finally, multiply -√ with -√:

-√ * -√ = √ * √ = √^2 = 2.

Putting it all together, we have:

(-14) + (-7√) + (2√) + 2
= -14 - 5√ + 2
= -12 - 5√.

Therefore, the exact answer is -12 - 5√.
Divide 86√2 . Provide an exact answer.(1 point)
Responses
a 43–√ 4 start root 3 end root
b 46–√ 4 start root 6 end root 83–√
c 8 start root 3 end root
d This expression is already simplified and cannot be divided further.
To divide 86√2, we need to simplify the expression further.

We can divide 86 by the square root of 2:

86 ÷ √2 = 86/√2

To rationalize the denominator, we can multiply both the numerator and denominator by the conjugate of √2, which is √2. This will eliminate the square root in the denominator.

(86/√2) * (√2/√2) = (86√2) / (2)

Dividing 86√2 by 2:

(86√2) / 2 = 43√2

Therefore, the exact answer is 43√2, which is option a) 43–√4 start root 3 end root.